The prevalence of urolithiasis in subjects undergoing computer tomography in selected referral diagnostic centers in Mogadishu, Somalia - Dirie, Najib Isse; Adam, Mohamed Hussein; Garba, Bashiru; Dahie, Hassan Abdullahi; Sh. Nur, Maryan Abdullahi; Mohamed, Fartun Yasin; Mohamud, Abdirahman Khalif; Hassan, Jihaan (Frontiers in Public Health, 2023)
Introduction and Objectives: Somalia was predicted to be in the global stone belt with high urolithiasis prevalence. We aimed to determine the prevalence of urolithiasis and their demographic and Computer Tomography (CT) characteristics among subjects under CT scans in Mogadishu, Somalia. Materials and Methods: From March 2014 to November 2022, a total of 7276 patients who underwent an Abdominopelvic non-contrast CT scan for various indications were retrospectively reviewed. The mean age was 45.6 years with a standard deviation of 21.1 (range 0.2–110 years). Patients were subdivided into two categories; adults (≥18 years) and pediatric (≤17 years). Results: Of the 7276 patients, 1075 (14.8%) were diagnosed with urolithiasis. Among those with urolithiasis, 702 (65.3%) were males, and 373 (34.7%) were females. And of that, adults accounted for 92.7% while children were 7.3%. Renal stones (nephrolithiasis) were the most common, representing 57% followed by ureteric stones at 35.5%, making upper urinary stones 92.5%. Bladder stones were 70 (6.5%), of these, 26 of them (37%) were accompanied by benign prostatic hyperplasia (BPH). There were 10 urethral stones (0.9%) recorded in the study, all were found in male patients, 8 localized in prostatic, and 2 in the bulbar urethra. The overall mean stone size was 13.2mm, and 60% of them ranged from 5-22 mm. Only 24% of the patients were asymptomatic. Single stones were almost 70% while Staghorn calculi were 8.2%. More than 60% of the patients with urolithiasis showed some degree of hydronephrosis ranging between mild to severe. Conclusion: A CT scan-based urolithiasis prevalence indicates 14.8% in Mogadishu, Somalia, these results are consistent with the probability calculation of the WofE (weights-of-evidence methodology) based on several risk factors including temperature, climate change, mineral deposit, drinking water quality, and distribution of carbonated rocks. Considering the high prevalence of the disease, Somalia needs to invest more in prevention and treatment facilities while also training urologists that are capable of utilizing minimally invasive techniques in the country. Keywords: Urolithiasis, Prevalence, Non-contrast Computer Tomography, Mogadishu, Somalia Running title: Non-contrast CT scan-based prevalence of urolithiasis in Mogadishu, Somalia